Long-term care residents: the relationship between perceived justice and quality of life, satisfaction with staff, and psychological sense of community - Brescian, Natalie E., author; Vacha-Haase, Tammi, advisor; Rickard, Kathryn, committee member; Swaim, Randall, committee member; McGrew, John, committee member (Colorado State University. Libraries, 2010)
The present study explored the relationship among justice perceptions and mental health-related quality of life (QOL), satisfaction with long-term care (LTC) facility staff, and psychological sense of community (PSOC) in LTC residents. The study was exploratory in nature because it examined the experience of living in LTC based on a new framework. One-hundred and seven participants completed a survey containing items measuring justice, PSOC, satisfaction with staff and QOL. Data was analyzed using correlational and hierarchical regression analyses. Results indicated that the three types of justice (interactional, procedural, and distributive) demonstrated positive correlations with mental-health related QOL, satisfaction with staff, and PSOC. Additionally, two separate hierarchical regression analyses revealed that the relationship between justice and satisfaction with staff, and PSOC were significant after controlling for functional status and physical health-related QOL. Physical health-related QOL emerged as the only predictor of mental health-related QOL. Implications for LTC residents and directions for future research are discussed.
Covers not scanned.
Keywords: Older people -- Long-term care -- Psychological aspects; Community psychology; Quality of life